Future of built environment - Uda Nagu, Suzieana (2012)
FINAL-YEAR Architecture student Chong Chun Jiat had not enjoyed a good night's sleep in days. As the programme director of the 24th Architectural Workshop - the recent instalment of the most anticipated event among architecture students in Malaysia - Chong was understandably under immense pressure to perform.